Low-complexity architecture for Chase soft-decision Reed-Solomon decoding - Yung-Kuei Lu; Shen-Ming Chung; Shieh, Ming-Der (Technical Papers of 2014 International Symposium on VLSI Design, Automation and Test, 2014)
Soft-decision decoding of Reed-Solomon (RS) codes can achieve good coding gain by using the probability information from the channel. Among various soft-decision algorithms, the Chase algorithm has moderate performance and rational complexity and hence is usually designed for hardware implementation. Chase-type decoders, however, still have much higher complexity than that of conventional hard-decision decoders. This paper proposes a reduced-complexity Chase (RCC) algorithm and its corresponding high-speed VLSI architecture. With the developed fast and efficient decision-making scheme, the resulting hardware complexity is greatly reduced while keeping the error correction performance comparable to that of the Chase decoders. For a (255, 239) RS code, experimental results show that the proposed decoder design has at least 44.6% improvement in area-time complexity as compared to the related works.